Studying Pest Control through Traditional Methods - Amit Kumar,; Prof. (Dr.) Sivanand Singh, (International Journal of Scientific Research in Science and Technology, 2025)
Traditional pest control methods, often rooted in indigenous knowledge passed down through generations, offer sustainable and environmentally-friendly approaches to agricultural and household pest management. These methods are often low-cost, using locally available resources, minimizing reliance on synthetic chemicals, and promoting biodiversity. However, challenges related to standardization, scalability, and integration with modern practices exist. This research paper explores traditional pest control techniques, categorizes them based on their mode of action, and analyzes their potential for modern agriculture, especially within the context of Integrated Pest Management (IPM). By studying the effectiveness and scientific validation of these practices, the aim is to contribute to the development of sustainable pest management strategies that can improve agricultural productivity while minimizing environmental and health risks.
Keywords: Pest Control; Pest Management